WildFARM Tools: Assessment of the wildlife value chains and zoonotic risk in wildlife farms - Ha Thi Thanh Nguyen; Thang Nguyen-Tien; Sinh Dang-Xuan; Unger, Fred; Hu Suk Lee; Lindahl, Johanna F.; Phuong Thi Minh Nguyen; Terfa, Zelalem; Huyen Thi Thanh Le; Vuong Nghia Bui; Tung Duy Dao; Hung Nguyen-Viet; et al. (International Livestock Research Institute, 2024)
Wildlife farming has become a significant economic driver, contributing to income generation, food production, and biodiversity. However, the close proximity between farmed wildlife and humans creates a heightened risk of zoonotic disease transmission. Understanding the knowledge, attitudes and risky behaviours of wildlife farmers and other key actors in the wildlife value chains is crucial to mitigating these risks. In low and middle-income countries, surveillance of zoonotic pathogens from farmed wildlife is hindered by the lack of standardized data collection tools and reporting systems. To address this gap, we developed and adapted tools specifically designed for key actors along different wildlife value chains. The data collection tools are consisting quantitative questionnaires, biosafety observation checklist, and qualitative key informal interviews, and focus group discussion guides with different key actors along the wildlife value chains. These tools are being used to collect comprehensive data on demographics, farming practices, knowledge, attitudes, and behaviours related to zoonotic disease prevention, consumption and collection of wildlife products, health status, biosafety measures, and perception on wildlife and zoonotic disease management. The data collected through these tools will inform the development of One Health interventions and enhance coordination among stakeholders to reduce the risk of zoonotic diseases associated with wildlife farming, trade, and consumption.